2012
DOI: 10.1016/j.neurobiolaging.2011.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Vascular inflammation in cerebral small vessel disease

Abstract: Cerebral small vessel disease (CSVD) is considered to be caused by an increased permeability of the blood-brain barrier and results in enlargement of Virchow Robin spaces (VRs), white matter lesions, brain microbleeds, and lacunar infarcts. The increased permeability of the blood-brain barrier may relate to endothelial cell activation and activated monocytes/macrophages. Therefore, we hypothesized that plasma markers of endothelial activation (adhesion molecules) and monocyte/macrophage activation (neopterin) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
151
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(161 citation statements)
references
References 42 publications
5
151
1
4
Order By: Relevance
“…Very few studies used cellular biomarkers of endothelial dysfunction. Finally, with the exception of a few studies, 52,66,74,79,84 only selective biomarkers involved in different points of the complex pathways linking together endothelial dysfunction and coagulation system/inflammation processes were analyzed. It should be underlined that the assessment of individual biomarkers cannot provide information on relative contributions by the distinct pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Very few studies used cellular biomarkers of endothelial dysfunction. Finally, with the exception of a few studies, 52,66,74,79,84 only selective biomarkers involved in different points of the complex pathways linking together endothelial dysfunction and coagulation system/inflammation processes were analyzed. It should be underlined that the assessment of individual biomarkers cannot provide information on relative contributions by the distinct pathways.…”
Section: Discussionmentioning
confidence: 99%
“…76 Interestingly, in the Austrian Stroke Prevention Study, ICAM-1 proved to be associated with a robust outcome measure, i.e., WMH progression at both 3 and 6 years. 85 Rouhl et al 84 studied several endothelial biomarkers finding higher levels of E-selectine, neopterin, and VCAM-1 in patients with lacunar infarcts and/or WMH. Considering MRI markers of SVD, PVS resulted independently associated with neopterin and MB with E-selectine.…”
Section: 61mentioning
confidence: 99%
“…33 Another environmental factor, inflammation (namely, chronic inflammation) is also related to SVD pathology (Figure 1), including lacunar stroke, enlarged perivascular space, and subsequent WMH. 34,35 Consequently, many studies have focused on the relationship between inflammation and SVD. It has been demonstrated that inflammation primarily targets endothelial cells and results in BBB breakdown, 36,37 probably because of neopterin and cytokines secreted by activated monocytes/ macrophages, 34 subsequently disrupting the extracellular matrix.…”
Section: Inflammation Infection and Brain-gut Axis In Svdmentioning
confidence: 99%
“…34,35 Consequently, many studies have focused on the relationship between inflammation and SVD. It has been demonstrated that inflammation primarily targets endothelial cells and results in BBB breakdown, 36,37 probably because of neopterin and cytokines secreted by activated monocytes/ macrophages, 34 subsequently disrupting the extracellular matrix. 38 The question is what triggers inflammation in the first place?…”
Section: Inflammation Infection and Brain-gut Axis In Svdmentioning
confidence: 99%
“…9 Indeed, we recently demonstrated that immunoglobulin G antibodies to oxidized low-density lipoproteins were elevated in patients with cerebral small vessel disease as compared with patients with uncomplicated hypertension. 10 Interestingly, protective immunoglobulin M antibodies were lower in patients with cerebral small vessel disease as compared with uncomplicated hypertension patients.…”
mentioning
confidence: 98%